Building the Future: Transforming ASN Offices and Housing - Edy Gunawan; Muhammad Iqbal Mutaqin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This article discusses the management of state-owned assets (BMN) in Indonesia, focusing on the strategies of the Ministry of Finance in optimizing asset use, managing office and residential areas, and establishing a corporate identity. The COVID-19 pandemic has prompted the Ministry of Finance to optimize the use of BMN by transforming the workspace from a cubicle model to an open space using the Activity Based Workplace (ABW) concept. This program aims to increase the effectiveness and efficiency of BMN management and create a more collaborative and productive work environment. In addition, the Ministry of Finance is also striving to meet the housing needs of Civil Servants (ASN) by building and renovating official houses and collaborating with various parties to provide decent housing. The enforcement of corporate identity through the standardization of BMN artefacts is expected to foster a sense of ownership of the organization, form a positive perception, nurture employee loyalty, foster spirit, and increase work productivity.